Barriers to Women’s Participation in Tourism Development in Nongkosawit Tourism Village - Rizki Hidayati; Tri Yuniningsih; Gandisa Pangestuti Kiswoyo; Mary S Mangai (Universitas Sultan Ageng Tirtayasa, 2026)
Community participation in tourism village development reflects an inclusive, gender-responsive approach. However, in practice, women and men still do not have equal access and opportunities in tourism governance and decision-making processes. This study aims to analyze the barriers to women’s participation in tourism development in Nongkosawit Tourism Village, Gunungpati District, Semarang City, using Licuanan’s socio-cultural barriers theory. The study employed a qualitative case study approach and a purposive sampling technique. The selection of female informants was based on Semarang Mayor Regulation Number 27 of 2023 on gender mainstreaming. Data was collected through in-depth interviews, Focus Group Discussions (FGDs), and observations, and analyzed using triangulation, content analysis, and NVivo software for coding and project map visualization. The findings show that women have participated in tourism village development through the provision of local culinary products, MSME product processing, culture- and local wisdom-based tourism services, homestay management, karawitan performances, and tourism promotion. However, women’s involvement remains concentrated in operational and supporting roles, while strategic positions in tourism village governance are still dominated by men. Barriers to women’s participation are influenced by structural and socio-cultural factors, including women’s social status, limited access to strategic employment, gender-based division of labor, and women’s double burden in domestic and public spheres. Therefore, affirmative policies are needed through women’s representation quotas in tourism village management and Musrenbang forums, leadership and digital marketing training, the establishment of women’s tourism business groups, and the provision of childcare facilities to support more inclusive and equitable participation in tourism village development.